The potential of Melaleuca cajuputi extract as an antibacterial, anti-iflammatory and osteogenic agent in oral regenerative therapy: Potensi ekstrak Melaleuca cajuputi sebagai agen antibakteri, antiinflamasi dan osteogenik dalam terapi regeneratif rongga mulut - Rieuwpassa, Irene Edith; Hamka, Dinda Cindrahati; Izzah, Agnes Dea Ugie Wihdatul; Salamah, Ummi; Budiawan, Utami Putri; Anwar, Vina Maulydia; N, Nur Syabina Octavia Gamal; Zakiyah, A. Fadhilah Putri (Makassar Dental Journal PDGI Makassar, 2025)
Oral regenerative therapy requires agents with antibacterial and osteogenic properties to address hard tissue damage caused by infection or trauma. Galam leaves (Melaleuca cajuputi), a plant native to Southeast Asia, are known to contain bioactive com-pounds such as flavonoids, polyphenols, alkaloids, and saponins that support tissue healing. This article systematically reviews the potential of galam leaf extract as an antibacterial, anti-inflammatory, and osteogenic agent in oral regenerative therapy, based on literature evaluating the biological activity and safety of galam leaf extract, particularly against oral pathogenic bacteria and its ability to stimulate osteogenesis. Galam leaf extract has been proven to have antibacterial activity against S.mutans, Lactobacil-lus plantarum, and P.gingivalis. Its combination with tricalcium silicate cement increases the number of odontoblast-like cells and lymphocytes. Toxicity tests indicate that the extract is safe for topical use even at high concentrations. It is concluded that galam leaf extract is a candidate for the development of biomaterials in regenerative therapy due to its multifunctional and safe properties.